2015
DOI: 10.13189/ujar.2015.030301
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Zinc in Maize (Zea Mays L.) through Soil and Foliar Application

Abstract: Maize (Zea mays L.) is considered as high nutrient demanding crop and needs balanced nutrition. It is also regarded sensitive to zinc deficiency. Zinc is mostly deficient in soils and application of zinc fertilizer is required to explore its full potential. Crop species and even cultivars within species vary in their Zn requirement. A field experiment was conducted during spring 2011 at Agronomic Research Area, University of Agriculture, Faisalabad, Pakistan to evaluate the comparative efficacy of Zn uptake an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
4
17
1
Order By: Relevance
“…Similar results are also reported by Khan et al (2004) and Malavolta (2006) who indicated that basal application of Zn improved the biological yield of crop. The results of our experiment regarding harvest index are contradicted with the findings of Ehsanullah et al (2015) and Potarzycki and Grzebisz (2009) who stated that foliar application of Zn significantly enhanced the harvest index. In our study, compared to control, a significant increase was found in grain Zn concentration of maize.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar results are also reported by Khan et al (2004) and Malavolta (2006) who indicated that basal application of Zn improved the biological yield of crop. The results of our experiment regarding harvest index are contradicted with the findings of Ehsanullah et al (2015) and Potarzycki and Grzebisz (2009) who stated that foliar application of Zn significantly enhanced the harvest index. In our study, compared to control, a significant increase was found in grain Zn concentration of maize.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar findings were also reported by Tariq et al (2002) who revealed that soil application at 20 kg Zn ha -1 increased the grain yield of maize. Our findings also corroborate the results of Grzebisz et al (2008) and Ehsanullah et al (2015) who reported that foliar application of Zn enhanced the grain yield and its component. The increase in biological yield with basal application at 15 kg ZnSO 4 ha -1 might have been due to enhanced growth on account of protein synthesis or higher activity of carbonic anhydrase (DELL; WILSON, 1985).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Shaharoona et al (2006) observed the biomass improved up to 68.4% in maize when the seeds were inoculated by Azotobacter compared to control. Vegetative growth and consequently biological yield are highly dependent on consumption of micro and macro chemical elements by the maize plant (Ehsanullah et al, 2015), so application of fertilizers that contain those elements leads to an increase in biological yield of maize. Protein content (%)…”
Section: Dry Mattermentioning
confidence: 99%